Bismuth titanate / bismuth stannate / bismuth composite photocatalytic material as well as preparation method and application thereof

By introducing Sn4+ into bismuth titanate/bismuth stannate/bismuth composite photocatalytic material, building a heterogeneous interface and optimizing the energy band structure, the problem of low carrier separation efficiency of layered bismuth oxide photocatalytic material is solved, and efficient photocatalytic activity and visible light response are achieved.

CN119819287APending Publication Date: 2025-04-15XIAN UNIV OF TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202510075102.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Laminated bismuth oxide photocatalytic materials have problems with low carrier separation efficiency and poor visible light response, which limits their large-scale application.

Method used

Using bismuth titanate/bismuth stannate/bismuth composite photocatalytic material, by introducing Sn4+ into the bismuth layered Bi4Ti3O12 system, a heterogeneous interface is constructed, the energy band structure and built-in electric field are optimized, and the separation and utilization of photogenerated carriers are promoted.

Benefits of technology

It significantly improves the oxidation potential and carrier separation rate of photocatalytic materials, improves its photocatalytic activity and degradation efficiency under visible light, and has good application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819287A_ABST
    Figure CN119819287A_ABST
Patent Text Reader

Abstract

The invention discloses a bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, the structural formula of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material is Bi < 4 > Ti < 3-0.5 > x Sn < x > O < 12 > / Bi < 2 > Sn < 2 > O < 7 > / Bi, and the value of x is 0.05-0.5. The invention further discloses a preparation method of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, Bi2O3, TiO2, SnO2 and NaCl-KCl molten salt are mixed, subjected to ball milling, dried and sintered, sintered powder containing molten salt is obtained, washed, centrifuged and dried, and the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material is obtained. The Bi4 (Ti, Sn) 3O12 / Bi2Sn2O7 / Bi composite photocatalytic material prepared by the preparation method disclosed by the invention has high oxidation potential, high photon-generated carrier separation efficiency and high visible light absorption, can show excellent photocatalytic activity, and shows a good application prospect in the aspect of photocatalytic degradation of organic pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of piezoelectric-photocatalytic material preparation, and specifically relates to a bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, and also relates to a preparation method and application of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material. Background Art Photocatalytic technology has become an important means to control environmental pollution and alleviate energy crisis due to its mild reaction conditions, simple operation and no secondary pollution. As the core of this technology, the selection, design and preparation of photocatalytic materials are very critical, which will directly determine its final performance and application. Among the many photocatalytic materials, the Aurivillius crystal structure is a layered bismuth oxide, composed of (Bi2O2) 2+ Layer and perovskite (A n-1 B n O 3n+1 ) 2- The layer composition is bismuth titanate (Bi4Ti3O 12 ) as an example, the conduction band is mainly formed by the hybridization of the 3d orbital of titanium (Ti) and the 2p orbital of oxygen (O). The bottom energy level of its conduction band is relatively high, which enables it to effectively absorb ultraviolet light. The valence band is mainly formed by the hybridization of the 6s orbital of bismuth (Bi) and the 2p orbital of oxygen (O). The 6s orbital of Bi makes the top of the valence band have a higher energy level, which helps to improve the oxidation ability of photogenerated holes. The band gap of bismuth titanate is around 2.8eV, and it mainly absorbs ultraviolet light. Its band gap determines its photocatalytic activity in the ultraviolet light region. At present, layered bismuth oxide photocatalytic materials still have technical bottlenecks such as low carrier separation efficiency and poor visible light response, which seriously limits the large-scale application of such materials.

[0002] Layered bismuth oxides easily form electric dipole moments due to the misalignment of the positive and negative charge centers in their crystal cells, showing a piezoelectric effect. The resulting polarized electric field can induce rapid separation of bulk charges. Therefore, layered bismuth oxides with piezoelectric effect can effectively collect mechanical energy in the environment and convert it into electrical energy, thereby inducing redox reactions. On the one hand, catalysis is achieved with the help of the piezoelectric effect of the material itself, that is, the coupling of piezoelectric-photocatalytic effects; on the other hand, lattice distortion is induced by ion doping to enhance the built-in electric field and promote the separation of carriers. At the same time, the phase transition temperature is regulated to near room temperature, so that it exhibits high piezoelectric-photocatalytic efficiency at room temperature.

[0003] In addition, the band gap structure of the material can be adjusted by means of the construction of heterogeneous interfaces and the plasma resonance effect of metal surface modification, so that the material can absorb a wider spectrum of light, including ultraviolet light and visible light, improve the utilization rate of sunlight, and promote the separation of photogenerated electrons and holes, and reduce the recombination of photogenerated electrons and holes. Bismuth stannate (Bi2Sn2O7) is a rare earth oxide with a fluorite-type cubic structure, which has unique photocatalytic properties and chemical stability. Theoretically, the band gap of bismuth stannate is about 2.5eV, and the bottom energy level of its conduction band is low, which enables bismuth stannate to absorb a wider range of visible light. Similar to bismuth titanate, the 6s orbit of Bi increases the energy level of the top of the valence band, which is conducive to the oxidation reaction of photogenerated holes. In addition, metal Bi will strongly absorb the incident light, excite the electrons on the surface of the metal nanoparticles, and make them participate in the photocatalytic reaction. Therefore, this composite material is prepared, and its band gap structure is optimized, the light absorption range is increased, the built-in electric field is enhanced, and the separation of photogenerated electrons and holes is promoted, thereby significantly improving the catalytic performance. Summary of the invention

[0004] The purpose of the present invention is to provide a bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, which improves the oxidation potential and carrier separation rate of the photocatalytic material and can exhibit excellent photocatalytic activity.

[0005] Another object of the present invention is to provide a method for preparing a bismuth titanate / bismuth stannate / bismuth composite photocatalytic material.

[0006] The third object of the present invention is to provide the application of bismuth titanate / bismuth stannate / bismuth composite photocatalytic material in degrading organic pollutants.

[0007] The technical solution adopted by the present invention is that the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material has a structural formula of Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi, the value of x is 0.05-0.5. Preferably, the value of x is 0.20.

[0008] Another technical solution adopted by the present invention is a method for preparing a bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, which is specifically implemented according to the following steps: Step 1, according to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi stoichiometric ratio, Bi2O3, TiO2, SnO2 raw materials were weighed respectively, and fully mixed with NaCl-KCl molten salt, ball milled, and dried to obtain a raw material mixture; Step 2, transferring the raw material mixture in step 1 to an alumina crucible for sintering to obtain a sintered powder containing molten salt; Step 3, washing the sintered powder in step 2 alternately with deionized water and anhydrous ethanol for several times, centrifuging, and drying to obtain a bismuth titanate / bismuth stannate composite photocatalytic material.

[0009] The present invention is also characterized in that: In step 1, the ball milling time is 10 to 16 hours, the ball milling speed is 400 to 600 r / min, the ball milling medium is deionized water; the drying temperature is 60 to 100 ° C, and the drying time is 6 to 24 hours.

[0010] In step 2, the sintering temperature is 600-1000°C and the sintering time is 2 h.

[0011] In step 3, the centrifugal speed is 8000-15000 r / min, and the centrifugal time is 1-5 min.

[0012] In step 3, the drying temperature is 60 to 100 °C, and the drying time is 6 to 24 h.

[0013] The beneficial effects of the present invention are: (1) The present invention uses the molten salt method to achieve Bi4(Ti,Sn)3O 12 The construction of heterogeneous interface of Bi2Sn2O7 / Bi composite photocatalytic material is achieved by 12 Sn is introduced into the system 4+ , directly obtained bismuth titanate / bismuth stannate / bismuth composite photocatalytic materials with heterogeneous interfaces, which have the advantages of wide raw material sources, low production cost, few experimental steps, simple operation, low requirements for equipment, manpower and site, and are expected to achieve industrial production; (2) Bi4(Ti,Sn)3O prepared by the present invention 12 The composite photocatalytic material of the heterogeneous interface of Bi2Sn2O7 / Bi presents a uniform two-dimensional thin sheet. The reduction of the sheet thickness helps the electrons to migrate quickly to the surface of the catalyst, significantly improving its carrier separation efficiency. At the same time, the thin sheet easily provides more active sites and surface area, which is beneficial to the adsorption of reactants on the catalyst surface and the reaction activity. (3) Bi4(Ti,Sn)3O prepared by the present invention 12 / Bi2Sn2O7 / Bi heterogeneous composite photocatalytic materials are obtained by optimizing the energy band junction and Bi4Ti3O 12 The piezoelectric effect and phase transition temperature enhance the migration efficiency of photogenerated carriers. The conduction band of Bi2Sn2O7 is low and can be used as an electron capture material, while Bi4Ti3O 12 The valence band is higher and can capture holes. This energy band arrangement helps to increase the driving force of the photocatalytic reaction. (4) Bi4(Ti,Sn)3O prepared by the present invention12 / Bi2Sn2O7 / Bi composite photocatalytic material has high oxidation potential, high photogenerated carrier separation efficiency and high visible light absorption, can exhibit excellent photocatalytic activity, and shows good application prospects in photocatalytic degradation of organic pollutants. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The Bi4(Ti,Sn)3O prepared in Example 1 12 XRD pattern of / Bi2Sn2O7 / Bi; Figure 2 is a photocatalytic degradation efficiency curve diagram of Rhodamine B degradation in Example 1 and the comparative example; Figure 3 is a photocatalytic degradation rate curve diagram of Rhodamine B degradation in Example 1 and the comparative example; Figure 4 is a photocatalytic degradation efficiency curve diagram of Rhodamine B degradation in Example 3 and Example 5; Figure 5 Bi4Ti3O prepared in Comparative Example 1 12 SEM images of Figure 6 The Bi4(Ti,Sn)3O prepared in Example 1 12 SEM spectrum of / Bi2Sn2O7 / Bi. DETAILED DESCRIPTION

[0015] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0016] The bismuth titanate / bismuth stannate / bismuth composite photocatalytic material of the present invention has a structural formula of Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi, the value of x is 0.05~0.5, and preferably, the value of x is 0.20.

[0017] The preparation method of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material of the present invention is specifically implemented according to the following steps: Step 1, according to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi stoichiometric ratio: weigh Bi2O3, TiO2, SnO2 raw materials with purity above 95.00% respectively, mix them thoroughly with NaCl-KCl molten salt, and ball mill them for 10-16h, the speed of ball mill is 400-600r / min, the ball milling medium is deionized water, and dry them at 60-100℃ for 6-24h to obtain a raw material mixture; The mass ratio of NaCl and KCl in NaCl-KCl molten salt is 1:1; Step 2, transferring the raw material mixture in step 1 into an alumina crucible, and sintering at 600-1000° C. for 2 h to obtain a sintered powder containing molten salt; Step 3, washing the sintered powder in step 2 alternately with deionized water and anhydrous ethanol for several times, centrifuging at a centrifugal speed of 8000-15000 r / min and a centrifugal time of 1-5 min; drying at a drying temperature of 60-100 ° C and a drying time of 6-24 h to obtain a bismuth titanate / bismuth stannate composite photocatalytic material.

[0018] The present invention uses NaCl-KCl salt melt as a reaction medium to prepare Bi4(Ti,Sn)3O by chemical reaction of Bi2O3, TiO2 and SnO2 at high temperature. 12 / Bi2Sn2O7 / Bi composite material. The reaction mechanism during the preparation process is as follows: First, at high temperature, the molten salt melts, the precursor dissolves in the molten salt and is evenly distributed. Under the action of the molten salt, Bi4Ti3O 12 Crystals of Bi2Sn2O7 and Bi4(Ti,Sn)3O7 gradually form and are uniformly compounded in the molten salt medium. The molten salt provides an environment conducive to crystal growth and compounding, ensuring the high crystallinity and uniformity of the material. After the reaction is completed, the mixture is cooled to room temperature and the molten salt re-solidifies. The solidified molten salt is removed by water washing or alcohol washing to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite materials. The washing process needs to ensure the complete removal of molten salts and by-products to obtain pure composite photocatalytic materials.

[0019] The microstructure of the material structure of the present invention presents a two-dimensional flake shape, which is mainly derived from the preparation of Bi4(Ti,Sn)3O by molten salt method. 12 In the process of preparing Bi4(Ti,Sn)3O7 / Bi composite materials, the molten salt not only acts as a reaction medium, but also plays a role in uniformly distributing the precursors, promoting chemical reactions and controlling the morphology of the products. The molten salt provides a stable liquid phase environment, promoting the growth and recombination of crystals, and finally forming a highly crystalline and uniformly composite Bi4(Ti,Sn)3O7 / Bi composite material. 12 / Bi2Sn2O7 / Bi material. This method provides an efficient and controllable way to synthesize photocatalytic materials, which is expected to play an important role in environmental governance and energy fields.

[0020] Bi4(Ti,Sn)3O prepared by the present invention 12 / Bi2Sn2O7 / Bi composite materials can effectively remove Rhodamine B under visible light, such as Figure 2 and Figure 3As shown in Figure 2, the catalytic process combines the S-scheme photocatalytic mechanism with the built-in electric field enhanced by lattice distortion. Bi4(Ti,Sn)3O is directly generated by Sn introduction and regulation. 12 / Bi2Sn2O7 / Bi composite material, the matching of its energy bands makes the composite material present a high reduction potential and strong oxidation ability of holes. A potential difference (built-in electric field) will be formed between the interfaces of the two materials, which greatly promotes the directional movement of carriers, thereby achieving the purpose of separation. Finally, different active substances are formed on the surfaces of the two materials. These active substances directly degrade pollutants in water. In addition to ensuring that both materials can absorb visible light, they can also effectively separate the photogenerated electrons and holes formed inside the composite material.

[0021] Example 1 The preparation method of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material of the present invention is specifically implemented according to the following steps: Step 1, according to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi (x=0.2) stoichiometric: 3.6562 g NaCl with a purity of 99.00%, 4.6875 g KCl with a purity of 99.00%, 2.33 g Bi2O3 with a purity of 99.99%, 0.5790 g TiO2 with a purity of 99.90%, and 0.0377 g SnO2 with a purity of 99.00% were weighed respectively, put into a nylon jar, and milled for 16 hours in a ball mill at 400 rpm using zirconium balls and anhydrous ethanol as a ball milling medium, dried in a drying oven at 80 °C for 15 hours, ground in a mortar for 30 minutes, and passed through an 80-mesh sieve to obtain a raw material mixture; Step 2, placing the raw material mixture in an alumina crucible, compacting it with an agate rod, covering it, placing it in a muffle furnace, heating it to 900° C. at a heating rate of 5° C. / min, pre-firing it for 2 hours, and naturally cooling it to room temperature to obtain a sintered powder containing molten salt; Step 3, add deionized water to the sintered powder containing molten salt, ultrasonically wash, centrifuge (speed 8000 r / min, time 3min), repeat the above steps 5 to 6 times, and then add anhydrous ethanol to the test tube and repeat 2 to 3 times. The above sample was dried in an oven at 60℃ for 2h to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite materials.

[0022] Example 2 According to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi (x = 0.1) stoichiometric: 3.6562 g of NaCl with a purity of 99.00%, 4.6875 g of KCl with a purity of 99.00%, 2.33 g of Bi2O3 with a purity of 99.99%, 0.5890 g of TiO2 with a purity of 99.90%, and 0.0188 g of SnO2 with a purity of 99.00% were weighed respectively. The other steps were the same as those in Example 1 to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite photocatalytic material.

[0023] Example 3 According to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi (x = 0.22) stoichiometric: 3.6562 g of NaCl with a purity of 99.00%, 4.6875 g of KCl with a purity of 99.00%, 2.33 g of Bi2O3 with a purity of 99.99%, 0.5770 g of TiO2 with a purity of 99.90%, and 0.0414 g of SnO2 with a purity of 99.00% were weighed respectively. The other steps were the same as those in Example 1 to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite materials.

[0024] Example 4 According to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi (x = 0.5) stoichiometric: 3.6562 g of NaCl with a purity of 99.00%, 4.6875 g of KCl with a purity of 99.00%, 2.33 g of Bi2O3 with a purity of 99.99%, 0.5491 g of TiO2 with a purity of 99.90%, and 0.0942 g of SnO2 with a purity of 99.00% were weighed respectively. The other steps were the same as those in Example 1 to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite materials.

[0025] Example 5 According to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi (x = 0.22) stoichiometric: 3.6562 g of NaCl with a purity of 99.00%, 4.6875 g of KCl with a purity of 99.00%, 2.33 g of Bi2O3 with a purity of 99.99%, 0.5770 g of TiO2 with a purity of 99.90%, and 0.0414 g of SnO2 with a purity of 99.00% were weighed respectively, put into a nylon jar, and milled for 16 hours in a ball mill at 400 rpm using zirconium balls as grinding balls and anhydrous ethanol as ball milling media, and then dried in a drying oven at 80°C for 15 hours, ground in a mortar for 30 minutes, and passed through a 80-mesh sieve to obtain a raw material mixture; the raw material mixture was placed in an alumina crucible, compacted with an agate rod, covered, placed in a muffle furnace, and heated to 700 at a heating rate of 5°C / min. ℃ for 2 hours, and naturally cooled to room temperature to obtain a sintered powder containing molten salt; the other steps are the same as in Example 1 to obtain Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite materials.

[0026] Comparative Example 1 According to Bi4Ti3O 12 The stoichiometric ratio of NaCl with a purity of 99.00% was 3.6562 g, KCl 4.6875 g, Bi2O3 2.330 g, and TiO2 0.5984 g, which were mixed and ground thoroughly. The other steps were the same as those in Example 1 to obtain Bi4Ti3O 12 Photocatalytic materials.

[0027] Comparative Example 2 According to the stoichiometric ratio of Bi2Sn2O7, 3.6562 g of NaCl with a purity of 99.00%, 4.6875 g of KCl, 2.330 g of Bi2O3, and 1.5152 g of SnO2 were weighed respectively, mixed and ground thoroughly, and the other steps were the same as in Example 1 to obtain a Bi2Sn2O7 photocatalytic material.

[0028] Figure 1 Bi4(Ti,Sn)3O 12 XRD patterns of Bi4Ti3O / Bi2Sn2O7 / Bi composites 12 , Bi2Sn2O7, and Bi correspond to standard PDF cards No.47-0398, No.32-1203, and No.51-0765, respectively, which confirms the successful preparation of the composite photocatalytic material.

[0029] Figure 2 and Figure 3 They are Bi4(Ti,Sn)3O 12 / Bi2Sn2O7 / Bi composite photocatalytic materials and comparative samples Bi4Ti3O12 The photodegradation efficiency curves and degradation rate constants of Bi4(Ti,Sn)3O7 under visible light for degradation of Rhodamine B. 12 / Bi2Sn2O7 / Bi、Bi4Ti3O 12 The photodegradation efficiencies of Bi2Sn2O7 for rhodamine B were 87%, 53.5% and 48.7%, respectively; the corresponding first-order kinetic constants were 0.028 min -1 、0.0185min -1 and 0.0146 min -1 The above results show that: 12 / Bi2Sn2O7 / Bi composite photocatalytic material has the best photodegradation activity and degradation rate, and can effectively remove organic pollutants (Rhodamine B), mainly because the material has high oxidation potential, high photogenerated carrier separation efficiency and high visible light absorption.

[0030] Figure 4 The Bi4(Ti,Sn)3O obtained in Example 3 and Example 5 12 The photodegradation efficiency curve of Rhodamine B degradation under visible light of Bi2Sn2O7 / Bi composite material. It can be seen that when the Sn introduction amount is 0.22, the catalytic efficiency of the composite material obtained by sintering at 700℃ is slightly higher than that at 900℃, indicating that when the crystalline structure is formed, the temperature has little effect on its catalytic efficiency.

[0031] Example 6 The molten salt method used in the present invention is a method for preparing high-quality Bi4(Ti,Sn)3O 12 This is an effective method for preparing / Bi2Sn2O7 / Bi composite photocatalytic materials. Through high-temperature melting and chemical reaction, the precursors are evenly distributed in the molten salt medium and react to generate the target material. The molten salt plays multiple roles in the preparation process, including dissolving, promoting reaction and controlling morphology, ensuring the high crystallinity and uniformity of the material.

[0032] Figure 5 and Figure 6 The SEM images of the samples prepared in Comparative Example 1 and Example 1 show that the prepared samples are all two-dimensional flakes. 12 The thickness of the lamellae of the / Bi2Sn2O7 / Bi composite material is significantly thinner. The reduction in the lamellae thickness helps electrons to quickly migrate to the surface of the catalyst and participate in chemical reactions, significantly improving its carrier separation efficiency.

Claims

1. Bismuth titanate / bismuth stannate / bismuth composite photocatalytic material, characterized in that: Its structural formula is Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi, the value of x is 0.05~0.

5.

2. The bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 1, characterized in that: Preferably, the value of x is 0.

20.

3. The method for preparing the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 1, characterized in that: Follow the steps below to implement it: Step 1, according to Bi4Ti 3-0.5x Sn x O 12 / Bi2Sn2O7 / Bi stoichiometric ratio, Bi2O3, TiO2, SnO2 raw materials were weighed respectively, and fully mixed with NaCl-KCl molten salt, ball milled, and dried to obtain a raw material mixture; Step 2, transferring the raw material mixture in step 1 to an alumina crucible for sintering to obtain a sintered powder containing molten salt; Step 3, washing the sintered powder in step 2 alternately with deionized water and anhydrous ethanol for several times, centrifuging, and drying to obtain a bismuth titanate / bismuth stannate composite photocatalytic material.

4. The method for preparing the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 3, characterized in that: In the step 1, the ball milling time is 10 to 16 hours, the ball milling speed is 400 to 600 r / min, the ball milling medium is deionized water; the drying temperature is 60 to 100° C., and the drying time is 6 to 24 hours.

5. The method for preparing the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 3, characterized in that: In the step 2, the sintering temperature is 600-1000° C. and the sintering time is 2 h.

6. The method for preparing the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 3, characterized in that: In step 3, the centrifugal speed is 8000-15000 r / min, and the centrifugal time is 1-5 min.

7. The method for preparing the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to claim 3, characterized in that: In step 3, the drying temperature is 60 to 100° C., and the drying time is 6 to 24 hours.

8. Use of the bismuth titanate / bismuth stannate / bismuth composite photocatalytic material according to any one of claims 1 to 7 in degrading organic pollutants.

Citation Information

Patent Citations

  • Ti2LaxBi2-xO7 or Bi2SnxTi2-xO7 photocatalysis material, preparation method and application thereof

    CN101204651A

  • Bismuth titanate / bismuth oxide photocatalyst as well as preparation method and application thereof

    CN108772053A

  • BiSnSbO6 powder catalytic material and BiSnSbO6-TiO2 composite photocatalytic material

    CN110252280A

  • Composite photocatalyst and method for applying composite photocatalyst to treatment of unsymmetrical dimethylhydrazine wastewater

    CN110639499A

  • Doped bismuth titanate niobate nanosheet and preparation method thereof

    CN113797932A